An Analysis Of Students’ Problem-Solving Skills Based On Mathematic Disposition During The Covid-19 Pandemic - Asmaul Husna; Yudhi Hanggara (STAI Hubbulwathan Duri, 2022)
One of the psychological factors that affect problem solving ability is mathematical disposition. Students need a positive mathematical disposition that will make them persistent in facing problems and developing good habits in learning mathematics. The condition of Covid-19 outbreak emphasizes the importance of positive mathematical disposition and good problem solving skills. This study aims at describing students' mathematical problem-solving skills based on mathematical dispositions during the Covid-19 Pandemic. This research belongs to a qualitative descriptive study that involved 27 students in the fourth semester as the research subject. The research data were collected from questionnaires, test descriptions, and interviews. The questionnaire results were used to categorize students' mathematical dispositions. It was followed by an interview with two students selected from each group of mathematical disposition categories. The results of tests and interviews were analyzed based on the category of students' mathematical dispositions. The results of this study showed the three categories of students' mathematical dispositions i.e high, moderate, and low. The students with high mathematical dispositions show good mathematical problem-solving skills because they can perform all indicators of mathematical problem-solving abilities. The students of moderate mathematical disposition were only able to perform the 2-3 indicators. The students of the low mathematical disposition category only fulfilled the 1-2 indicators.